Effects of orthostatic hypotension on cognition in Parkinson disease. (3rd January 2017) - Centi, Justin; Freeman, Roy; Gibbons, Christopher H.; Neargarder, Sandy; Canova, Alexander O.; Cronin-Golomb, Alice
Abstract : Objective: To investigate the relation between orthostatic hypotension (OH) and posture-mediated cognitive impairment in Parkinson disease (PD) using a cross-sectional and within-group design. Methods: Individuals without dementia with idiopathic PD included 18 with OH (PDOH) and 19 without OH; 18 control participants were also included. Neuropsychological tests were conducted in supine and upright-tilted positions. Blood pressure was assessed in each posture. Results: The PD groups performed similarly while supine, demonstrating executive dysfunction in sustained attention and response inhibition, and reduced semantic fluency and verbal memory (encoding and retention). Upright posture exacerbated and broadened these deficits in the PDOH group to include phonemic fluency, psychomotor speed, and auditory working memory. When group-specific supine scores were used as baseline anchors, both PD groups showed cognitive changes following tilt, with the PDOH group exhibiting a wider range of deficits in executive function and memory as well as significant changes in visuospatial function. Conclusions: Cognitive deficits in PD have been widely reported with assessments performed in the supine position, as seen in both our PD groups. Here we demonstrated that those with PDOH had transient, posture-mediated changes in excess of those found in PD without OH. These observed changes suggest an acute, reversible effect. Understanding the effects of OH due to autonomic failure on cognition is desirable, particularly as neuroimaging and clinical assessments collect data only in the supine or seated positions. Identification of a distinct neuropsychological profile in PD with OH has quality of life implications, and OH presents itself as a possible target for intervention in cognitive disturbance.